2018
DOI: 10.1212/wnl.0000000000004801
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial progenitor cells enhance blood–brain barrier permeability in subacute stroke

Abstract: The functional properties of EPCs are associated with enhanced subacute permeability of BBB and improved clinical outcome after acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 29 publications
0
33
0
Order By: Relevance
“…In fact, previous studies in mice have demonstrated a weak but significant association between angiogenesis and CBF, which is more pronounced after seven days [15] and prolongs at least up to 21 days [16]. This subacute association of angiogenesis with CBF is reinforced by recent findings associating blood-brain barrier permeability of stroke patients at seven days with good clinical outcome and more proficient EPCs [2], and are in line with our current results, where no association was found between EPCs and CBF at three months. Moreover, the interpretation of our data within these previous reports, support the notion that the hemodynamic impact of the EPCs can only be partially explained by the effect of angiogenesis on CBF [16], as could be expected considering the anatomically restricted area of neoangiogenesis in comparison to the more widespread evaluation implicated in CBF.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In fact, previous studies in mice have demonstrated a weak but significant association between angiogenesis and CBF, which is more pronounced after seven days [15] and prolongs at least up to 21 days [16]. This subacute association of angiogenesis with CBF is reinforced by recent findings associating blood-brain barrier permeability of stroke patients at seven days with good clinical outcome and more proficient EPCs [2], and are in line with our current results, where no association was found between EPCs and CBF at three months. Moreover, the interpretation of our data within these previous reports, support the notion that the hemodynamic impact of the EPCs can only be partially explained by the effect of angiogenesis on CBF [16], as could be expected considering the anatomically restricted area of neoangiogenesis in comparison to the more widespread evaluation implicated in CBF.…”
Section: Discussionmentioning
confidence: 80%
“…We isolated EPCs from 18 mL of peripheral venous blood collected in the first day and at day seven after stroke onset in accordance to previously validated protocols [1,2]. Mononuclear cells (MNC) were isolated from peripheral blood by density gradient centrifugation using Lymphoprep™ density gradient medium.…”
Section: Isolation Of Epc Sub-populationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiogenesis plays a pivotal role in poststroke recovery; however, animal models have raised the possibility of hemorrhagic transformation as a potential complication of promoting new, immature vessels ( 14 ). Nonetheless, this link shows an apparent time-dependent response with acute disruption of the blood–brain barrier and hemorrhagic transformation in the first hours after stroke, whereas enhancing effective neoangiogenesis with improved outcomes in the subacute stage ( 8 , 15 ). These facts reinforce the need to define an optimized therapeutic window for the design of future phase III trials.…”
Section: Discussionmentioning
confidence: 99%
“… 17 18 In a later subacute stage, the BBBP relies on physiological recovery processes such as neoangiogenesis, as demonstrated in both animals 19 20 and humans. 21 Whereas the existence of this permeability process is unequivocal, its concrete evolution is not yet certain.…”
Section: Introductionmentioning
confidence: 99%